"Empty Chairs at Empty Tables": Disenfranchisement by Association. (March 2022) - Pitcho-Prelorentzos, Shani; Mahat-Shamir, Michal
The rise in research publications over the last few decades about disenfranchised grief has deepened our understanding of this field. Importantly, it raises awareness and validates human experiences of bereavement, which are often socially ignored, muted, and stigmatized. However, while researchers in the field actively engage in the task of "enfranchisement, " as they present their work at scientific conferences, they might experience what we term disenfranchisement by association in the academic sphere. Based on our own experience, this article will demonstrate the parallel pathways between disenfranchisement of bereaved individuals and disenfranchisement of disenfranchised grief researchers, as it emerges in three main expressions of disenfranchisement: reluctance to listen, shame and guilt inflicting, and demand for euphemism. A conclusive note on how to address this kind of disenfranchisement is suggested.